The sun and fifteen doorways of Phnom Rung - Komonjinda,S. (Cambridge University Press, 2015)
Phnom Rung was a Khmer-style Hindu temple complex. It was built in sandstone and laterite on the rim of an extinct volcano between the 10th and 13th centuries. At the beginning, the sanctuary was built as a dedication to Shiva. Following the abandonment of Phnom Rung (which was unrecorded) the sanctuary fell into ruin, and it was not until 1971 that it was restored using anastylosis. Phnom Rung Historical Park, along with the other temples Phimai and Muang Tum, have been on the tentative list for UNESCO World Heritage since 2004. Walking from the eastern side (front) to the western side of Phnom Rung takes the visitor through 15 doorways-those of the inner cloisters, the annex, the principal tower, and the inner sanctum. The centers of these doorways are perfectly aligned, with an azimuth of 84.5°. Every year thousands of people from Thailand and around the world travel to Phnom Rung to see the sun rising through its all of its 15 doorways. This event happens only twice a year, at the beginning of April and the beginning of September. Sunsets can also be seen through the doorways, in March and October. Each pair of sunrise-sunset events is separated by one lunar month. The possible meaning of this event has been investigated by both archaeologists and astronomers. Nothing is recorded about sunrise or sunset among the inscriptions at the site. Another issue is that the many and various structures remain within the complex, showing that constructions in this area spanned several centuries. However, it seems that the overall layout did have a significance, both astronomical and religious. © International Astronomical Union 2011.